The two Lasswells: implications for critical policy studies. Issue 2 (3rd April 2019) - Zittoun, Philippe
ABSTRACT: This contribution would like to discuss Torgeson's proposal by interrogating the two faces behind Lasswell's work on the one hand, and the multiple perspectives behind critical policy studies on the other. Paradoxically, answers to this question are either too difficult or too easy.